Method of manufacturing a diamond composite
Patent Information
- Application Number
- CN202280084503.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-12-21
- Filing Date
- 2022-12-16
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-12-16
AI Technical Summary
[0008]已知增材制造或3D印刷适用于制作复杂的几何形状,尤其是具有空腔、内部孔洞和通道的几何形状,通过其它方式将难以实现这些几何形状和/或实现这些几何形状将非常昂贵
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
[0001] This invention relates to a method for manufacturing a diamond composite in which the residual infiltrant has been removed during the permeation step. Background Technology
[0002] Diamond composites are known in the art and can be used in many applications, such as cutting tools, mining drill bits, etc.
[0003] Diamond composites can be manufactured in various ways, for example, by forming a green body containing diamond particles and then allowing a penetrant (typically silicon) to react with some of the diamond particles at elevated temperatures to form a carbide binder (typically SiC) in which the diamond particles are embedded. This step can be carried out at high temperatures and pressures, but diamond composites can also be achieved by penetrants at lower pressures or even in a vacuum (depending on the type of composite required).
[0004] For diamond composites infiltrated under milder pressures, residual infiltrator left on the composite is a problem. If the final composite has pores or cavities, these are often filled with residual infiltrator, which then has to be removed. If thin and / or hollow details are printed, residual solidified silicon can also cause cracks and fractures due to the tensile forces generated in the sintered body as silicon expands during solidification. Residual infiltrator can also react with the graphite sintering trays in the sintering furnace, requiring more frequent replacement.
[0005] Excess penetrant can be removed mechanically, such as by sandblasting. Sandblasting is effective if the diamond compound does not contain any internal pores or channels. If the diamond compound contains internal pores or channels, sandblasting is insufficient, and residual penetrant must be removed by dissolving it in a strong acid such as HF. Both processes are complex and time-consuming, and the use of strong acids is particularly dangerous.
[0006] Residual penetrant may also cause the penetrated workpiece to adhere to the underlying material during the penetrating process, which requires additional steps to release the workpiece.
[0007] Residual penetrant is a problem for diamond composites of all shapes, but it is particularly problematic for shapes containing pores and cavities.
[0008] Additive manufacturing or 3D printing is known to be suitable for creating complex geometries, especially those with cavities, internal holes and channels, which would be difficult and / or very expensive to achieve by other means.
[0009] One object of the present invention is to provide a method for manufacturing diamond composites that minimizes residual penetrant to avoid the aforementioned problems. Summary of the Invention
[0010] This invention relates to a method for preparing diamond composites, comprising the following steps:
[0011] - Provide at least one diamond green body containing at least 25% by volume diamond particles and an organic binder;
[0012] - Provide penetrants;
[0013] - Place the at least one diamond green body together with a penetrant on a graphite crucible;
[0014] - Before and / or after placing the at least one diamond green body together with a penetrant on a graphite crucible, at least one debonding step is performed on the at least one diamond green body to form at least one debonded diamond green body;
[0015] - A permeation step is performed on the at least one debonded diamond green body, the permeation step being carried out for a time of 5 to 60 minutes in a vacuum or in the presence of a protective gas at a temperature between 1500 and 1680°C and a pressure of less than 50 mbar.
[0016] During the infiltration step, the graphite crucible is placed on a lower carbon source along with the at least one debonded diamond green body and the infiltrator.
[0017] Diamond green body refers to a body comprising diamond particles and an organic binder. The amount of diamond particles is at least 25% by volume, preferably between 30% and 75% by volume, and more preferably between 35% and 70% by volume of the green body.
[0018] In this paper, "debonded green body" refers to a diamond green body in which at least 60% of the organic binder has been removed.
[0019] The debonded diamond green body is placed together with the penetrant on a graphite crucible. The diamond green body can be placed directly on the graphite crucible, next to the penetrant, or on top of the penetrant. The distance between the debonded diamond green body and the penetrant should preferably be small enough that they are in direct contact with each other once the penetrant is in its molten state during the penetrant infiltration process.
[0020] The graphite crucible (also referred to as a boat) can be any type of foil, sheet, boat, or crucible suitable for infiltration in a furnace. The graphite crucible should be thin and / or porous enough to allow residual penetrant to pass through and reach the underlying carbon source. After infiltration, the graphite crucible has reacted with the penetrant and is primarily composed of the carbides of the penetrant; that is, if the penetrant is Si, the crucible will be converted to SiC during the infiltration process.
[0021] Preferably, graphite foil or sheets are used. Foil or sheets are suitable for several reasons. Sufficient thickness is readily available, and furthermore, since the graphite crucible is used only once, foil or sheets are cost-effective. The thickness of the graphite foil or sheet is preferably between 0.05 and 3 mm, more preferably between 0.1 and 2 mm, and most preferably between 0.1 and 0.5 mm.
[0022] In one embodiment of the invention, the graphite crucible is formed to surround the diamond green body. For example, if graphite foil is used, the foil is typically soft and can be wrapped around the diamond green body. This helps to prevent the carbon source from contaminating the surface of the diamond green body.
[0023] Optionally, the penetrant may be selected from silicon, silicon compositions, aluminum, and aluminum alloys. Preferably, the penetrant is Si. The penetrant may be provided as blocks, coarse powder, wafers, etc., preferably blocks or wafers. The amount of penetrant present is preferably in significant excess relative to the diamond green body, preferably exceeding 200% by weight of the amount of penetrant theoretically required to completely penetrate the diamond body. If the amount of penetrant is too small, the diamond composite will not be completely penetrated, and graphitization of the diamond will occur.
[0024] In one embodiment of the invention, the penetrant is silicon. Suitably, the penetrant may contain silicon with a purity greater than 99% by weight, and may be present in a substantial excess (greater than 200% by weight).
[0025] The penetrant is placed together with the debonded diamond green body on the graphite crucible. The penetrant should preferably be placed close to the debonded diamond green body so that it comes into contact with the green body when it melts.
[0026] The graphite crucible, along with the debonded diamond green body and the penetrant on top of it, is then placed on top of the carbon source, such that the graphite crucible is in contact with the carbon source. The carbon source can be any material primarily containing carbon, preferably at least 95% by weight. The addition of the carbon source should preferably be in excess of the penetrant used. This means that sufficient carbon source must be present to react with the total amount of penetrant. The amount of carbon source used also depends on the size and quantity of the diamond green body to be penetrated. If the amount of carbon source is too small, excess penetrant will still be present on the penetrated diamond composite, and the penetrated diamond composite may adhere to the graphite crucible.
[0027] The carbon source is preferably a carbon-containing powder. It can be provided as an agglomerated powder or as carbon particles. Preferably, the carbon source is carbon powder or graphite powder, more preferably carbon powder in the form of soot or carbon black. Preferably, the powder is not too dense so that the penetrant can react easily with the powder. The powder is typically placed on a tray inside the furnace, and the height of the powder bed should preferably be at least 5 mm, preferably at least 10 mm but less than the height of the tray, to prevent the penetrant from leaking onto the lower tray on which the carbon source is placed.
[0028] Prior to infiltration, the diamond green body undergoes at least one debonding step to form a debonded green body. Since the diamond green body contains a significant amount of organic binder, at least a substantial amount of the organic binder must be removed from the green body in a controlled manner before infiltration to avoid cracking. A substantial amount means, herein, the removal of at least 60%, preferably at least 70%, of the organic binder. In some cases, some residual organic binder may remain in the debonded diamond green body. If the debonding step is performed as a separate step and the diamond green body must be moved, some residual organic binder may contribute to the strength of the diamond green body, which would otherwise be prone to cracking during processing. In these cases, the residual organic binder may be removed in a second debonding step included at the beginning of the infiltration step, or it may remain in the diamond green body. If the debonded diamond green body contains any residual organic binder during infiltration, the carbon in the organic binder will react with the infiltrator during infiltration, thereby limiting the amount of diamond lost due to reaction with the infiltrator.
[0029] Before and / or after placing the at least one diamond green body together with the penetrant on a graphite crucible, at least one debonding step is performed on the diamond green body. Therefore, the debonding step can be performed as a separate step or incorporated into the penetrant step as a first step.
[0030] For larger workpieces, it may be advantageous to perform the debonding step in a separate furnace, which allows the adhesive to be removed slowly and thus avoids cracking.
[0031] Preferably, the debonding step is incorporated into the permeation step and carried out in the same furnace.
[0032] The debonding step may include heating the diamond green body to a first maximum temperature by gradually increasing the temperature. Optionally, the gradual temperature increase includes increments of 0.1 to 5°C / min, preferably 0.1 to 2°C / min. Optionally, the debonding is carried out in an environment selected from nitrogen, argon, hydrogen, and mixtures thereof. Air may also be used as the environment. Optionally, the maximum debonding temperature is in the range of 180°C to 550°C, preferably 200°C to 500°C. The debonding temperature depends on the environment (gas used) in which the debonding step is carried out, and also on the type of organic binder used. The time of the debonding step may vary considerably depending on the size of the diamond green body, the type of binder, the amount of binder, and the atmosphere. If the debonding step is too rapid, cracks may appear in the diamond green body. The debonding step typically lasts between 1 and 50 hours, preferably between 1 and 24 hours.
[0033] The permeation is preferably carried out at a temperature between 1500 and 1680°C, preferably between 1550 and 1660°C. The permeation is preferably carried out in a vacuum or in the presence of a protective gas at a pressure below 50 mbar for 5 to 60 minutes, preferably between 10 and 45 minutes. Vacuum herein refers to a pressure in the furnace below 5 × 10⁻⁶ mbar. -1 millibars, preferably below 5×10 -2 millibars. An inert gas can be used to protect the furnace, preferably argon, and the argon pressure is low, preferably below 50 millibars.
[0034] In one embodiment of the invention, the temperature is increased from the debinding temperature at a rate between 30 and 60°C / min, preferably between 30 and 55°C / min, until the desired penetration temperature is reached. If the temperature increase is too slow, graphitization of the diamond particles may occur before the penetrant melts. A rapid increase in temperature also causes the penetrant to melt rapidly, thereby achieving a low viscosity that is conducive to effective penetration.
[0035] Then, cooling is carried out in a controlled manner at a rate between 2 and 30°C / minute until the temperature is at least below 1300°C.
[0036] In one embodiment of the invention, at the end of the permeation step, before the temperature begins to decrease, an inert gas, such as Ar or N2, preferably Ar, is used to apply a pressure of less than 200 bar for at least 3 minutes, for example, between 3 and 45 minutes. This is done to further densify the composite and to allow the permeating agent to fully react to form carbides.
[0037] During the permeation step, some of the diamond particles are consumed due to the reaction with the permeating agent, but the diamond composite is suitable to contain at least 50% of the diamond particles present in the diamond green body.
[0038] The diamond green body can be formed using any method known in the art. Diamond green body herein refers to an unsintered body comprising diamond grains and an organic binder. Examples of suitable methods for manufacturing the diamond green body are 3D printing or compaction.
[0039] Any additive manufacturing method or 3D printing technology known in the art can be used, such as binder jetting, stereolithography, etc. Stereolithography is preferred. The exact printing parameters applied depend on the specific equipment used.
[0040] To form a printed body, a raw material comprising diamond particles and an organic binder is typically first formed. The composition and properties of the raw material, such as viscosity, depend on the type of composite to be printed, the type of organic binder, and the printing equipment used.
[0041] After printing, the printed green body is removed from the printing equipment and preferably cleaned to remove any excess powder and binder.
[0042] Depending on the type of printing technology used, a curing step may be performed on the printed body after the printing step.
[0043] For example, diamond green bodies produced by stereolithography are cured during the printing process and directly form the green body.
[0044] The diamond green body can also be manufactured using more conventional methods such as compaction. A slurry comprising the diamond grains and an organic binder (typically PEG (polyethylene glycol)) is then prepared. The slurry is then dried, preferably using spray drying or freeze drying, to form granules, which are then pressed into a green body using, for example, uniaxial pressing. The diamond green body obtained by compaction preferably has an organic binder content between 10 and 30 vol%, more preferably between 15 and 25 vol%.
[0045] The diamond particles used to prepare the diamond green body optionally have an average particle size of less than 200 µm, preferably less than 150 µm, and more preferably less than 100 µm. Optionally, the diamond particles may contain an average particle size in the range of 0.5 µm to 100 µm, preferably 1 µm to 100 µm, and more preferably 2 µm to 80 µm. In particular, the diamond particles may contain a bimodal or multimodal particle size distribution. Optionally, at least a portion of the diamond particles contain an average particle size of less than 30, 20, or 10 µm and at least a portion of the diamond particles contain a particle size of less than 100, 80, 70, 60, or 50 µm. Such an arrangement facilitates the optimization of diamond filling in the resulting green body and the final infiltrated article.
[0046] Organic binder, as used herein, refers to any binder commonly used in the manufacture of diamond green bodies. The composition of the organic binder may vary depending on how the diamond green body is manufactured.
[0047] The organic binder used in diamond green bodies manufactured by conventional compaction techniques is typically PEG (polyethylene glycol). Preferably, the organic binder is added in an amount between 10 and 30% by volume, more preferably between 15 and 25% by volume, of the diamond green body.
[0048] Binders used for 3D printing have a wider variety of compositions. The type of binder depends on the type of printing technology used. The amount of organic binder is typically between 5 and 60% by volume of the diamond green body, preferably between 5 and 58% by volume. The organic binder preferably comprises one or more organic compounds selected from the group consisting of resins, polysaccharides, polyvinyl alcohol, cellulose and cellulose derivatives, lignin sulfonates or esters, polyethylene glycol, polyvinyl derivatives, polyacrylates or esters, and mixtures thereof.
[0049] In one embodiment of the present invention using stereolithography (SLA), the binder content is preferably between 40 and 60% by volume, more preferably between 50 and 58% by volume. Organic binders used in stereolithography are typically photopolymers. This means that the polymer reacts and cures upon exposure to light, such as a UV lamp. Organic binders used in stereolithography can also be referred to as photocurable resins.
[0050] Other additives commonly found in diamond compounds, such as TiC, B4C, and ZrC, can also be added to the raw materials. The amount of additives is usually quite small, preferably less than 10% by weight of the total diamond green body, more preferably between 0.1% and 5% by weight. Attached Figure Description
[0051] Figure 1A schematic diagram of the setup before infiltration is shown, where A is the diamond green body, B is the infiltrator, C is the graphite crucible, D is the carbon source, and E is the dense graphite sintering tray.
[0052] Figure 2 The illustration shows a cubic-shaped diamond green body printed using stereolithography according to Example 1.
[0053] Figure 3 The example 1 shows a diamond composite in the shape of a cubic specimen after infiltration according to the invention.
[0054] Figure 4 The diamond green body and Si block of Example 2 are shown in a graphite crucible before infiltration.
[0055] Figure 5 The diamond composite of Example 2 is shown after infiltration in a graphite crucible.
[0056] Figure 6 A CT scan of the diamond composite in Example 2 is shown.
[0057] Example 1
[0058] Diamond green bodies are prepared using a 3D printing technique called stereolithography (SLA).
[0059] The feed material for the printing step was prepared from diamond powder and an organic binder. The diamond powder MBM-ULC from Hyperion was used, containing 80% by weight diamond grains with a grain size of 20-30 µm and 20% by weight diamond grains with a grain size of 4-8 µm.
[0060] 53% by volume of diamond powder was mixed with 47% by volume of an organic binder, which was a photoreactive resin supplied by Incus.
[0061] The 3D printing process was performed on an Incus Hammer HD35 3D printer with the following settings: a layer height of 40µm, an exposure intensity of 100 mW, an exposure time of 4.5 seconds, a blade temperature of 82°C, and a room temperature of 18°C.
[0062] The printed workpiece is a cubic test block containing different patterns and holes on its surface; see [link / reference]. Figure 2 .
[0063] After printing, the workpiece is removed and cleaned with IncuSol, and then pretreated in a vacuum at 120°C for 72 hours.
[0064] The diamond-containing green body was then placed together with the silicon penetrant on a 0.2 mm thick graphite foil (Mersen Papyex N98). The silicon penetrant was supplied in a large excess (>200 wt% of the green body) and was a crushed 4-8 mm Si wafer from ReSiTech.
[0065] Then, when the samples were placed in the furnace, some of the graphite foils were placed on top of a bed of carbon powder (ultrafine carbon black from IMCD Nordic) with a height of about 10 to 20 mm, while for comparison, some graphite foils were placed directly on a dense graphite sintering tray.
[0066] Debonding and infiltration were then carried out in the same furnace (GPS furnace). Debonding was performed by gradually heating the diamond green body to 500°C in H2 over approximately 7 hours. The temperature was then increased to 575°C and held for 1 hour. A vacuum was then applied, and the temperature was further increased. The temperature was increased from 700°C to 1350°C at a rate of 43°C / min. After holding the temperature at 1350°C for 2 minutes, the temperature was further increased to 1630°C at a rate of 37°C / min. After holding the temperature at 1630°C for 5 minutes, Ar was introduced into the furnace over a period of 10 minutes until the pressure reached 100 bar. The temperature was then held at 1630°C for another 10 minutes. The temperature was then reduced to 1000°C in a controlled manner at a rate of 7.8°C / min. The green body was then allowed to cool naturally.
[0067] When the sample is studied after infiltration, the sample according to the invention (i.e., in which a bed of carbon black powder is used) is easily removed and, after visual inspection, does not contain any excess Si. The pores in the print according to the invention are not filled with Si; samples without carbon powder under the graphite foil adhere to the graphite foil and must be removed with force. The pores are filled with Si.
[0068] Figure 3 One of the cubic test blocks after infiltration according to the present invention is shown.
[0069] All workpieces according to the present invention (with a carbon powder bed) and the comparative example (without a carbon powder bed) were permeated to full density.
[0070] Example 2
[0071] Pressed diamond green bodies are manufactured using the following raw materials.
[0072] Sample A
[0073] Diamond powder was dry-blended with fully deagglomerated TiC powder to form a homogeneous mixture. The powder mixture was a multi-peaked blend of MBM diamonds from Diamond Innovation, with particle sizes ranging from 6 to 80 µm, exhibiting high density during compaction. In addition to the diamond blend, 2% by weight of TiC was added to the slurry.
[0074] Using this mixture, PEG1500 and PEG4000 were added as temporary organic binders, Acusol 460 NK as a dispersant, and deionized water as the fluid to prepare a homogeneous slurry. The slurry was freeze-spray granulated and dried to obtain granules for pressing, with the amount of organic binder in the powder being 7.92% by weight, corresponding to 20% by volume. Using the compaction technique employed, the granules were uniaxially pressed into a green body to the highest possible green density, shaped like a tool tip commonly used in mining operations. The pressing pressure was approximately 20 kN, and the relative diamond density in the green body was approximately 66%. The green body was then slowly heated to 220°C in the presence of air to partially remove the PEG, thereby creating a partially debonded diamond green body with sufficient strength for further processing.
[0075] Samples B and C
[0076] Diamond powders were dry-blended together to form a homogeneous mixture. The diamonds were a mixture of 80 wt% 20-30 micrometer and 20 wt% 4-8 micrometer MBM grade diamonds from Diamond Innovations. Using this mixture, PEG1500 and PEG4000 were added as temporary organic binders, and deionized water was used as the fluid to prepare a homogeneous slurry. The slurry was spray-granulated to obtain particles for pressing, and the amount of organic binder in the powder was 9.26 wt%, corresponding to 23 vol%. Using the compaction technique employed, the particles were uniaxially pressed into a green body to the highest possible green density in the shape of a cylinder (RNGN) commonly used in metal cutting operations (2 mm diameter for sample B; 5 mm diameter for sample C). The force applied to compact the green body was typically 40-50 kN. The relative diamond density in the green body was approximately 60%. The relative diamond density in percentage form is calculated by dividing the mass of diamond in the green body (excluding temporary organic binders and other additives) by the volume of the green body obtained from the press tool drawing by dividing the X-ray density of diamond (3.52 g / cm³). 3Multiply by 100. Depending on the compaction technique and the shape of the green body, the density may vary slightly between different parts of the green body. The green body is slowly heated to 220°C in the presence of air to partially remove PEG, thereby creating a partially debonded diamond green body with sufficient strength for further processing.
[0077] Then, the diamond green body (sample AC) was subjected to the same infiltration step as described in Example 1, wherein the graphite foil was placed on top of a bed of carbon powder (ultrafine carbon black from IMCD Nordic) with a height of about 10 to 20 mm. For comparison, a piece of graphite foil containing the diamond green body (sample A) was placed directly on the dense graphite sintering tray.
[0078] All diamond composites (i.e., those in which a bed of carbon black powder is used) permeated according to the present invention are easily removed and do not contain any excess Si after visual inspection.
[0079] The different weights of diamond green bodies / diamond composites at different stages are shown in Table 1.
[0080]
[0081] Figure 4 The image shows a graphite foil before infiltration, along with Si penetrant and a pressed drill bit (sample A), and the infiltrated diamond composite after infiltration, as shown in the image. Figure 5 As shown. Figure 6 The image shown is from Invention 1, which uses X-ray computed tomography (CT).
[0082] The sample without carbon powder under the graphite foil (Comparative 1) adhered to the graphite foil and stuck together, and had to be removed by force.
[0083] As can be seen in Table 1, all workpieces according to the present invention (with a carbon black powder bed) and the comparison (without a carbon powder bed) were permeated to full density.
Claims
1. A method for preparing a diamond composite, comprising the following steps: - Provide at least one diamond green body containing at least 25% by volume diamond particles and an organic binder; - Provide penetrants; - Place the at least one diamond green body together with a penetrant on a graphite crucible; - Before and / or after placing the at least one diamond green body together with a penetrant on a graphite crucible, at least one debonding step is performed on the at least one diamond green body to form at least one debonded diamond green body; - A permeation step is performed on the at least one debonded diamond green body, the permeation step being carried out for a time of 5 to 60 minutes in a vacuum or in the presence of a protective gas at a temperature between 1500 and 1680°C and a pressure of less than 50 mbar. During the infiltration step, the graphite crucible is placed on a lower carbon source along with the at least one debonded diamond green body and the infiltrator.
2. The method of claim 1, wherein during the at least one debonding step, the at least one diamond green body is subjected to a temperature between 180 and 550°C for a period of time between 1 and 15 hours.
3. The method according to claim 1 or 2, wherein the graphite crucible is a graphite foil or sheet.
4. The method of claim 3, wherein the thickness of the graphite foil is between 0.05 and 3 mm.
5. The method according to claim 1 or 2, wherein the penetrant is Si.
6. The method according to claim 1 or 2, wherein the amount of the penetrant added exceeds 200% by weight of the at least one diamond green body.
7. The method according to claim 1 or 2, wherein the carbon source is toner.
8. The method of claim 7, wherein the toner is provided as a powder bed with a height of at least 5 mm.
9. The method according to claim 1 or 2, wherein at the end of the permeation step, before the temperature begins to decrease, a pressure of less than 200 bar is applied for at least 3 minutes using an inert gas.
10. The method according to claim 1 or 2, wherein the diamond green body is prepared by 3D printing.
11. The method of claim 10, wherein the diamond green body is prepared by stereolithography (SLA).
12. The method according to claim 1 or 2, wherein the diamond green body is prepared by compaction.
Citation Information
Patent Citations
Method for preparing diamond-silicon carbide electronic packaging material fast
CN102184873A
A method of producing a component of a composite of diamond and a binder
CN107922273A